STRATEGI DAKWAH DAN KEMAJEMUKAN MASYARAKAT - Sulkhan Chakim (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
Da ’wa is one of the essential parts of religiosity. According to Islam, every believer has the duty to preach Islamic teachings according to his capability. In the real life, this duty is actualized individually or in group. Da’wa includes inviting people to apply religious values and it is not merely done by Muslims. Followers of other religions also have such activity so that they should hcrve the same chance too. However, we should also realize that there are some contradictory doctrines such as tauhid, prophecy, and humanity.Every religion has an important role in human life which has dijferent culture. In spite of the true reasons, cultural diversity, including tribe, religion, and race, is often used to raise conflicts among people. Many conflicts in Indonesia, which seem to be religious conflicts, need to be viewed in relation to politics, economy, and socio- culture of the people. If religious conflicts really exist, it is necessary to build the spirit of togetherness based on the values of justice, freedom, and human rights. It is expected that the deeper the religious spirit, the deeper the sense of justice and humanity. As a result, in developing harmonious society, universal value-oriented da’wa is needed to create the spirit of togetherness and social solidarity.